Signet-ring cell gastric carcinoma in a dog - Mohamed Mustapha, Noordin; Low, P. K.; Lee, H. H.; Dhaliwal, Gurmeet Kaur; S., Abdul Jamil (Veterinary Association Malaysia, 2004)
Owing to its rarity, the clinical sign of chronic vomiting is usually diagnosed as foreign body obstruction or as an intestinal accident. Unfortunately, gastric carcinoma is usually never considered as a differential in such cases. This paper describes the pathology of signet-ring cell gastric carcinoma in a dog that had a history of chronic vomiting and haemetemesis along with associated haemogram and clinical biochemical changes pertaining to this tumour.